Is Ethnic Identity a Buffer? Exploring the Relations Between Racial Microaggressions and Depressive Symptoms Among Asian-American Individuals. Issue 1 (2nd January 2017) - Choi, Shinwoo; Lewis, Jioni A.; Harwood, Stacy; Mendenhall, Ruby; Huntt, Margaret Browne
ABSTRACT: This study explores the moderating role of ethnic identity in the relations between racial microaggressions and depressive symptoms. Using survey data from 353 Asian-American college students, we found that racial microaggressions significantly predicted depressive symptoms and accounted for 24% of the variance in a hierarchical multiple regression analysis. In addition, ethnic identity moderated the relations between racial microaggressions and depressive symptoms. Thus, ethnic identity buffers Asian-Americans against the negative mental health effects of racial microaggressions. Implications for research and practice in the field of social work are discussed.